Increased complications and morbidity in children with hemophagocytic lymphohistiocytosis undergoing hematopoietic stem cell transplantation. (18th January 2013) - Naithani, Rahul; Asim, Muhammad; Naqvi, Ahmed; Weitzman, Sheila; Gassas, Adam; Doyle, John; Schechter, Tal
Abstract Background Hematopoietic stem cell transplantation (HSCT) is the only curative option for patients with primary hemophagocytic lymphohistiocytosis (HLH) and for patients with secondary HLH who fail to respond to therapy. Methods Retrospective study of HSCT for HLH with focus on complications and outcome. Results Eighteen children (10 males), with a median age of 1.2 yr (5 months–16 yr), received HSCT for HLH. Fourteen children had primary HLH. Four children underwent transplant while not in remission. Sixteen received myeloablative and two received reduced intensity conditioning regimen. A high incidence of complications was found: 13 (72%) children had 22 episodes of culture‐proven infections; seven (38%) had hepatic veno‐occlusive disease; nine (50%) developed respiratory complications; and nine (50%) required intensive care unit admission. Eight children had acute graft‐versus‐host disease (GVHD), and three developed chronic GVHD. Three patients died from multi‐organ failure before day +100, and another patient died from pulmonary hemorrhage after day 100. Three patients failed to engraft (two developed recurrent HLH and died from complications after a second HSCT). Three of four children not in remission at the time of transplantation died. Actuarial survival at three yr was 61%. Conclusion HSCT for HLH carries significant risks with high infection, organ dysfunction, and ICU admissions rates.